The impact of hand washing and correlation with anxiety during the COVID-19 pandemic period - Athayde Nascimento, Gabriela; Stadler Rosa Lucca, Patrícia; de Bortoli Rota, Cristiane (Seven Editora, 2023)
Hand hygiene is one of the main measures concerning preventing the transmission of various diseases, among them, COVID-19 stands out here. It is known that its transmission occurs when there is contact of the virus with the mouth, nose, or eyes, through unwashed hands. It is noted, therefore, that keeping hands clean prevents infection and disease transmission. Considering this information, the present study discusses the impact of hand washing correlating with anxiety during the SARS-COV-2 (COVID-19) pandemic. Of understanding the essential social links that will undoubtedly contribute not only to professionals in the field but also to academics, teachers, and the community in general. As for the methodological criteria, the research was developed by the exploratory method- descriptive, the choice of method was fundamental in terms of data collection, as well as in the treatment of the information obtained, that is, the analysis of the population, and the investigated criteria, a moment in which the research is directed to the examination of the data of analytical and descriptive way. DOI: https://doi.org/10.56238/devopinterscie-153